EFFICACY AND SAFETY OF TRIAMCINOLONE ACETONIDE POSTERIOR SUBTENON INJECTION IN PATIENTS WITH DIABETIC MACULOPATHY - Jovanovic, Vera; Jovanović, Đorđe; Kujundžić, Borna; Karadžić, Jelena (Medicinski podmladak, 2017)
Introduction Diabetic maculopathy (DM) is the main cause of visual impairment of the working population. Optical coherence tomography and fluorescein angiography give us an precise insight into the retinal changes. In recent years pharmacological treatment of DM is increasing. Posterior subtenon application is accompanied by a smaller percentage of complications compared to intravitreal application. Aim The aim is to assess the efficacy and safety of triamcinolone acetonide (TA) posterior subtenon injection in the treatment of diabetic maculopathy by measuring intraocular pressure (IOP), central macular thickness (CMT) and visual acuity before and two months after. Material and methods The retrospective study included 49 patients admitted during 2016 for posterior subtenon injection of TA in the DM treatment at Daily Hospital for the treatment of vascular diseases of the eye and the macula Department of Ophthalmology, Clinical Center of Serbia. Data were collected from medical records on gender, age, type of retinopathy and visual acuity, IOP and CMT before and two months after intervention. Results The average age of patients was 63 ± 9.5 years, from 49 patients tested, 30.61% were female and 69.39 % were male. The frequency of NPDR in the study was 53.6%. There was a statistically significant difference in visual acuity and CMT before and two months after the intervention, but no correlation between improvement of visual acuity and CMT reduction. There wasn’t statistically significant difference in IOP before and two months after intervention. Conclusion The most common type of diabetic retinopathy in this study was NPDR. After posterior subtenon application of TA there was a significant increase in visual acuity and CMT reduction, but reduction of CMT isn’t connected with increase of visual acuity. Posterior subtenon TA application isn’t accompanied by a significant increase in IOP, and is an effective and relatively safe way of treating DM. Keywords: Diabetic maculopathy, visual acuity, central macular thickness, intraocular pressure